Leukapheresis for autologous stem cell transplantation: Comparative study of two different thawing methods WSCFD® Stem Cell Fast Thawer KW versus 37 °C thermostatic bath. Issue 3 (December 2015) - Becherucci, V.; Piccini, L.; Gori, V.; Bisin, S.; Bindi, B.; Ceccantini, R.; Pavan, P.; Cunial, V.; Ermini, S.; Brugnolo, F.; Bambi, F.
Abstract: Background: Leukapheresis for autologous stem cell transplantation represents an efficient technique for the reconstitution of haematopoietic system in patients subjected to a high-dose chemotherapy for the treatment of haematological malignancies. The current regulations emphasise first steps of leukapheresis procedure but do not recommend methods for thawing, only suggesting that it must be performed as soon as possible in a 37 °C thermostatic bath. Aim of the Study: We compared the classic method of thawing with an innovative and fully traceable method that uses WSCFD ® Stem Cell Fast Thawer KW. Materials and Methods: The first part of the study was focused on the thermodynamic process of the two methods, thawing 6 "simulated" leukapheresis (buffy coats of healthy donors cryopreserved with saline solution, 5% HSA and 5% DMSO) and analysing the thawing curve obtained, by using an inside probe. In the second part, we focused on the recovery of viable CD34+ cells and leukocytes, thawing 20 real leukapheresis from paediatric patients. In this phase we also analyse final core bag temperature, time of procedure, cellular recovery with ISHAGE single platform flow cytometry assay and clonogenic potential performing a CFU assay. Results: We found no significant differences between the two methods, both for thermodynamic aspect and cellular recovery. Thawing curves were similar and the paired Student's-t test used for statistical analysis showed a CD34+ cells recovery of 92.2% ± 11.4 using WSCFD ® versus 90% ± 11.1 of thermostatic bath. Data were similar even for leukocytes recovery (80.8% ± 9.5 with WSCFD ® and 79.2% ± 14.4 with thermostatic bath). All thawed products never exceeded the core temperature of 30 °C and no differences were found about the post-thaw clonogenic potential (614 × 10 4 ± 98.3 total CFU using WSCFD ® versus 592 × 10 4 ± 78.5 using thermostatic bath). The only difference observed was about the thawing time: WSCFD method requires a slightly longer time but, on the other hand, it correlates with reduced mean increase in temperature per minute, as a result of a more linear thawing curve. Conclusions: WSCFD ® can replace the 37 °C thermostatic bath thawing procedure for leukapheresis, providing more security and fully traceable process data.